Use of wearable devices for post-discharge monitoring of ICU patients: a feasibility study - Ryan R. Kroll; Erica D. McKenzie; J. Gordon Boyd; Prameet Sheth; Daniel Howes; Michael Wood; David M. Maslove; for the WEARable Information Technology for hospital INpatients (WEARIT-IN) study group (Journal of Intensive Care, 2017)
Abstract Background Wearable devices generate signals detecting activity, sleep, and heart rate, all of which could enable detailed and near-continuous characterization of recovery following critical illness. Methods To determine the feasibility of using a wrist-worn personal fitness tracker among patients recovering from critical illness, we conducted a prospective observational study of a convenience sample of 50 stable ICU patients. We assessed device wearability, the extent of data capture, sensitivity and specificity for detecting heart rate excursions, and correlations with questionnaire-derived sleep quality measures. Results Wearable devices were worn over a 24-h period, with excellent capture of data. While specificity for the detection of tachycardia was high (98.8%), sensitivity was low to moderate (69.5%). There was a moderate correlation between wearable-derived sleep duration and questionnaire-derived sleep quality (r = 0.33, P = 0.03). Devices were well-tolerated and demonstrated no degradation in quality of data acquisition over time. Conclusions We found that wearable devices could be worn by patients recovering from critical illness and could generate useful data for the majority of patients with little adverse effect. Further development and study are needed to better define and enhance the role of wearables in the monitoring of post-ICU recovery. Trial registration Clinicaltrials.gov, NCT02527408